Les plaisirs et les dangers d’enseigner la science-fiction au niveau universitaire - Barbara Bengels (ReS Futurae)
Science fiction, in all its aspects, but mostly through an exploration of themes such as politics, social, psychology, and ethics, deserves to be studied and taught in an academic classroom. This article points out the inherent and peculiar difficulties of teaching a body of literature that is changing even as we attempt to examine it, as well as the more political challenges that rise when trying to bring out such a course. Nevertheless, the article also describes the excitement and sense of wonder that emerge from teaching science fiction, a genre that keeps transforming and still accompanies us in our evolution.